Comments on the paper “Reconnaissance of Upper Jurassic Morrison Formation ichnofossils, Rocky Mountain Region, USA: Paleoenvironmental, stratigraphic, and paleoclimatic significance of terrestrial and freshwater ichnocoenoses” by Stephen T. Hasiotis - Bromley, Richard G. (2007)
Hasiotis (2004) has described and interpreted a relatively diverse and potentially very interesting ichnofauna from the Upper Jurassic Morrison Formation of the western United States. An effort was made by the author to bring the data to the reader, but, in our opinion, his analysis is seriously flawed and the resulting discussion and conclusions are not sufficiently supported by data...